H2O2 activation over Co substitution in Fe1-xS for tetracycline degradation: Effect of Co substitution. (June 2022) - Wang, Hanlin; Liu, Haibo; Zou, Xuehua; Sun, Fuwei; Wang, Luyao; Hu, Jingchao; Chen, Dong; Liu, Meng; Shen, Jianfei; Chen, Tianhu
Abstract: In this work, the effect of Co substitution in the Fe1-x S (CSP) on the activation of H2 O2 to degrade tetracycline (TC) is investigated. A series of CSP samples with different Co content are synthesized via a high-temperature sulfidation method and characterized by XRD, XPS, SEM, and electrochemical analysis. The result showed that low Co content (≤1%) promotes the catalytic activity of Fe1-x S, while excessive Co (1%﹤x ≤ 3%) inhibits its catalytic activity. The investigation of Behnajady-Modirshahla-Ghanbery kinetic model (BMG) showed that the maximum initial degradation rate of TC over 1.0% CSP/H2 O2 was 1.6 times than that of in CSP/H2 O2 system. The Box-Behnken with Response Surface Methodology was employed to verify optimum condition for TC degradation. The quenching experiments and ESR determined that ·OH, ·O2 − and 1 O2 were involved in TC degradation with the treatment of 1.0% CSP/H2 O2 system. Electrochemical analysis, ·OH quantification, and metal ion concentrations measure reveal that Co substitution accelerates electron transfer efficiency and Fe 2+ regeneration. Furthermore, nine intermediates are identified and the possible degradation pathway of TC is proposed. The unique effect of Co provides novel insight and efficient strategies for improving the reactivity of iron sulfide. Graphical abstract: Image 1 Highlights: Co substitution improved the degradation of tetracycline in Fe 1-x S/H 2 O 2 . The substitution of Co in Fe 1-x S structure accelerated Fe 2+ /Fe 3+ . The role of reactive oxygen species in 1% CSP/H 2 O 2 system is investigate. Possible intermediates and degradation pathway of tetracycline are reveals.